BRAND SOCIAL RESPONSIBILITY: SEBUAH PARADIGMA BARU DALAM MEMBANGUN MERK - I Putu Esa Widaharthana (JURNAL BISNIS HOSPITALITI, 2017)
When a brand reaches the consumer, the brand is already undergoing such a long journey. Starting from the time the company owns the brand standing, the process of creating a brand, the establishment of a factory, associated with the supplier, the production process, promotion, distribution, and others. Not surprisingly, in the process there are ethical issues that, intentionally or not, are violated by the company. Such as labor problems, suppliers’ emphasis, pollution, overpressive promotions to possible family problems arising from the brand.